Shipping Law Handbook - Bundock, Michael (informa law from Routledge, 2019)
Anyone who deals with shipping disputes requires access to a mass of source materials. These include international conventions, statutes and statutory instruments, arbitration rules, and the most commonly encountered bills of lading, charterparties, insurance clauses, guarantees and other contracts. Details of the parties to the international conventions are also required. The Shipping Law Handbook collects all this material in one convenient and easy-to-use volume.